Analisis Pemahaman Konsep Matematis Siswa SMA Berkepribadian Introvert dan Ekstrovert pada Soal Berbasis Etnomatematika Bangunan Masjid Besar Kanjeng Sepuh Sidayu - Lukmanul Khakim; Luluk Faridah; Khafidhoh Nurul Aini (Lembaga Pengembangan Kinerja Dosen, 2025)
This research started from the difference in understanding of mathematical concepts found in students in grades XI-1 of SMA Kanjeng Sepuh Sidayu. The main purpose of this study is to analyze students' understanding of mathematical concepts based on extroverted and introverted personalities, with an ethnomathematical approach on the building of the Kanjeng Sepuh Sidayu Mosque. The research subjects consisted of four students who were selected with two personality categories, namely two students with introverted personalities and two students with extroverted personalities, which were determined through a personality questionnaire. Data collection techniques were carried out using questionnaires to find out personality types, mathematical concept understanding tests, and in-depth interviews to further explore students' understanding. The results showed that there were significant differences in the understanding of mathematical concepts between students with introverted and extroverted personalities. Students with introverted personalities show good ability to meet indicators 1, 3, and 5. This indicator includes the ability to restate a concept, provide examples and non-examples of a concept, and apply concepts or logarithms in problem solving. Students with extroverted personalities, on the other hand, excel in indicators 1, 2, and 4. This indicator includes the ability to restate a concept, classify objects according to the concept, and use and choose certain procedures or operations in solving problems. This study provides insight that the understanding of mathematical concepts is not only influenced by cognitive abilities alone, but also by students' personality factors. Introverted and extroverted personalities affect the way they absorb and apply mathematical concepts. Therefore, it is important for educators to pay attention to these differences in designing teaching approaches that suit the characteristics of the students.